Near-wall hindered diffusion in convective systems: transport limitations in colloidal and nanoparticulate systems - Sokolov, S; Kätelhön, E; Compton, R (American Chemical Society, 2016)
Redox flow cells have a significant potential as efficient, scalable energy storage and use of nano-materials is likely to increase the energy density even further. Efficient cell design requires understanding of mass transport effects and for colloidal systems the theoretical assumptions commonly used for molecular species require re-evaluation. In the present work the effect of near-wall hindered diffusion is investigated in the convective-diffusive system of a colloidal suspension of nanoparticles. The rotating disk electrode system is used as a model due to wide applicability of the technique for the battery testing. A major influence of near-wall hindered diffusion is observed in the resulting concentration profiles of the nanoparticles (aqueous concentration as a function of distance) and the current responses in the case of the colloidal suspensions, and the finding is likely to have a significant impact on the understanding of physical processes underlying the practical cell design and modelling.